The relationship of age and place of delivery with postpartum contraception prior to discharge in Mexico: A retrospective cohort study - Darney, Blair G. (Contraception, 2016)
OBJECTIVES: To test the association of age (adolescents vs. older women) and place of delivery with receipt of immediate postpartum contraception in Mexico. STUDY DESIGN: Retrospective cohort study, Mexico, nationally representative sample of women 12–39 years old at last delivery. We used multivariable logistic regression to test the association of self-reported receipt of postpartum contraception prior to discharge with age and place of delivery (public, employment based, private, or out of facility). We included individual and household-level confounders and calculated relative and absolute multivariable estimates of association. RESULTS: Our analytic sample included 7022 women (population, N = 9,881,470). Twenty percent of the population was 12–19 years old at last birth, 55% aged 20–29 and 25% 30–39 years old. Overall, 43% of women reported no postpartum contraceptive method. Age was not significantly associated with receipt of a method, controlling for covariates. Women delivering in public facilities had lower odds of receipt of a method (Odds Ratio = 0.52; 95% Confidence Interval (CI) = 0.40–0.68) compared with employment-based insurance facilities. We estimated 76% (95% CI = 74–78%) of adolescents (12–19 years) who deliver in employment-based insurance facilities leave with a method compared with 59% (95% CI = 56–62%) who deliver in public facilities. CONCLUSION: Both adolescents and women ages 20–39 receive postpartum contraception, but nearly half of all women receive no method. Place of delivery is correlated with receipt of postpartum contraception, with lower rates in the public sector. Lessons learned from Mexico are relevant to other countries seeking to improve adolescent health through reducing unintended pregnancy. IMPLICATIONS: Adolescents receive postpartum contraception as often as older women in Mexico, but half of all women receive no method.